Evaluating the efficacy of dilute povidone-iodine versus normal saline for preventing surgical site infections following appendectomy: a prospective observational study in Ghanaian tertiary hospital - Sulemana Abdul-Latif; Joseph Yorke; Samuel Gyasi Brenu; Joseph Kwaku Oppong; Tonnies Abeku Buckman; Francis Somiah-Kwao Aitpillah; Jonathan Laryea; Gifty Kwakye; Michael Ofoe Adinku; Frank Enoch Gyamfi; Kwabena Agbedinu; Francis Akwaw Yamoah; et al. (BMC Surgery)
Abstract Background and Aims: Surgical site infection (SSI) remains a common postoperative complication for patients with acute appendicitis. This study aimed to compare the effectiveness of dilute povidone-iodine and normal saline in preventing post-appendectomy surgical site infections. Methods The study included 224 consecutive patients who underwent open appendectomy for acute appendicitis between October 2020 and December 2021 at Komfo Anokye Teaching Hospital in Ghana. Patients were randomly assigned to have irrigation with either povidone iodine or normal saline after appendectomy. The surgical wounds were assessed for infection using the Southampton wound grading system at 5 days post-surgery till 30 days. Result The mean age of the patients was 30.8 ± 14.4 years. The overall incidence of SSI was 8.04% (10.7% in the N/S group and 5.4% in the PI group). Both groups had a higher percentage of male patients (58% in the N/S group and 58.9% in the PI group). The mean length of hospital stays for patients with and without SSI was 10.11 ± 5.06 days and 4.69 ± 2.07 days respectively. The mean length of stay for the N/S group and PI group patients was 5.25 ± 2.95 days and 5.02 ± 2.81 days respectively. The mean cost for patients with and without SSI was GHC3,813.64(US$238.3) and GHC2,364.45 (US$147.7) respectively. Conclusion We conclude that there was no difference in SSI rates when comparing normal saline and povidone-iodine as irrigant fluids in patients undergoing an open appendectomy.